Spleen-preserving splenic lymph node dissection in radical total gastrectomy - Jie, Zhigang; Li, Zhengrong; Cao, Yi; Liu, Yi; Jiang, Mengmeng; Lin, Liangqing; Zhang, Guoyang (Chinese Journal of Cancer Research; Vol 25, No 4 (August 24, 2013): Chinese Journal of Cancer Research, 2013)
Radical gastrectomy has been recognized as the standard surgical treatment for advanced gastric cancer, and essentially applied in a wide variety of clinical settings. The thoroughness of lymph node dissection is an important prognostic factor for patients with advanced gastric cancer. Splenic lymph node dissection is required during D2 radical gastrectomy for upper stomach cancer. This is often accompanied by removal of the spleen in the past few decades. A growing number of investigators believe, however, that the spleen plays an important role as an immune organ, and thus they encourage the application of a spleenpreserving method for splenic hilum lymph node dissection.